New Global Perspectives on Industrial Engineering and Management International Joint Conference ICIEOM-ADINGOR-IISE-AIM-ASEM - Mula, Josefa; Barbastefano, Rafael; Díaz-Madroñero, Manuel; Poler, Raúl.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the proceedings of the 3rd International Joint Conference - ICIEOM-ADINGOR-IISE-AIM-ASEM (IJC2017) "XXIII International Conference on Industrial Engineering and Operations Management", "International ADINGOR Conference 2017", "International IISE Conference 2017", "International AIM Conference 2017" and "International ASEM Conference 2017", which took place at UPV (Universitat Politècnica de València) from July 6th to 7th, 2017. This joint conference is the result of an agreement between ABEPRO (Associação Brasileira de Engenharia de Produção), ADINGOR (Asociación para el Desarrollo de la Ingeniería de Organización), IISE (Institute of Industrial and Systems Engineers), AIM (European Academy for Industrial Management) and ASEM (American Society for Engineering Management). Consisting of papers on new global perspectives on industrial engineering and management, the book offers an interdisciplinary view of industrial engineering and management. The topics covered include: strategy and entrepreneurship, quality and product management, modelling and simulation, knowledge and project management, logistics, as well as production, information and service systems.
Part 1: Strategy and Enterpreneurship -- Chapter 1. Long Term Capacity Planning: The Comparison Between the Net Present Value, Return on Investment and Unitary Cost for Scale Analysis -- Chapter 2. Investigating the Impact of Process Innovation over Proﬁtability and Productivity: A Food Sector Application -- Chapter 3. The Importance of Using Alternative Energy Sources within a New Global Perspective -- Chapter 4. Strategies Adopted by Social Enterprises to Overcome Operations Resources Constraints: the Case of Vintage for a Cause -- Chapter 5. Developing a Scale to Measure Quality in Public Services Transport -- Chapter 6. A Model and a Methodology for the Systematization of Continuous Improvement of Logistics Processes in World-Class Companies -- Part 2: OR, Modelling and Simulation -- Chapter 7. Mapping the Perception of Users as the Usability of Smartphones: Benchmarking Features Through the Borda Count Method -- Chapter 8. Quality of Life in Latin America and Asia: An Economic Complexity Approach Between 2010 and 2014 -- Chapter 9. The Eﬃciency of Public Expenditures on Education: a Data Envelopment Analysis of Brazilian Federative Units Between 2011 to 2014 -- Chapter 10. Using Simulated Annealing to Solve the Daily Drayage Problem with Hard Time Windows -- Chapter 11. State of the Art on Arduino and RFID -- Chapter 12. Identifying the Main Uncertainties in the Agri-food Supply Chain -- Chapter 13. Environmental and Financial Improvements Due to the use of Ecodesign - In one Furniture Industry -- Part 3: Quality and Product Management -- Chapter 1 4. Competitive Priorities in the Hotel Sector of Sinop - Located in Northern Mato Grosso - Brazil -- Chapter 15. Motivators and Barriers for Using Design Thinking in NPD -- Chapter 16. Implantation of Total Productive Maintenance: A Case Study in the Manufacturing Industry -- Chapter 17. Analysis of Water Consumption in Cosmetic Factories in Brazil -- Chapter 18. Analysis of the Results of Lean Manufacturing Implementation in a Metal-Mechanical Company from Panambi - Rio Grande do Sul - BRAZIL -- Part 4: Knowledge and Project Management -- Chapter 19. Design of a Model for the Analysis of Hidden Costs in International Projects. Application to the Energy Sector -- Chapter 20. The Portfolio Management and Inﬂuence in Projects of Decisions -- Chapter 21. USA, Europe and Pharmerging Countries: a Panorama of Pharmaceutical Innovation.
Keywords: Industrial engineering; Production engineering; Computer simulation; Mathematics -- Data processing; Electronic data processing -- Management; Industrial and Production Engineering; Computer Modelling; Computational Science and Engineering; IT Operations